Kinetic Characteristics of the Oxidation of Non-Food Municipal Solid Waste; Solid Fuel Chemistry; Vol. 54, iss. 1 - Larionov K. B. Kirill Borisovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Vedyagin A. A. Aleksey Anatolievich; Gubin V. E. Vladimir Evgenievich (2020, 2020)
Title screen